THE ROLE OF FIRM SIZE, PRICE EARNING RATIO AND PROFITABILITY TO IDIOSYNCRATIC VOLATILITY: EVIDENCE FROM BANKING INDUSTRY IN INDONESIA - Dahyang Ika Leni Wijayani; Aulia Rizki Walidina; Totok Ismawanto; Devy Ayu Kusuma Wardani (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2023)
This study analyzes the effect of company size, price earnings ratio, and profitability on idiosyncratic volatility in state-owned banks listed on the Indonesia Stock Exchange in the period from 2011 to 2020, We use multiple regression analysis to tested the hypothesis. Firm size was measured by the natural logarithm of total assets, price earnings ratio by the comparison between market price and earnings per share, and profitability by return on equity. Idiosyncratic volatility is the fluctuation of stock price results form company specific information, measured by market regression model. Results show that size of the company, price earnings ratio and profitability have a negative and significant effect on idiosyncratic volatility. The increase of company size, price earnings ratio and profitability, consequently will lower the idiosyncratic volatility. From theoretical perspective, the finding of this research complied with three theories: valuation theory, prospect theory and life cycle theory whereas from managerial perspective, the business can effectively manage its assets and equity while carrying out its activities, resulting in strong fundamentals that may lower the amount of idiosyncratic risk.